Tropical forests are facing increasing risks of exposure to critical temperature thresholds - Nina van Tiel; Gaston Lenczner; Mukund P. Rao; Charlotte Grossiord; Devis Tuia (Proceedings of the National Academy of Sciences, 2026)
Understanding how close tropical tree species are to critical temperature thresholds that might impede photosynthetic activity is vital in a world where heat waves have become more severe and frequent. Using remotely sensed surface temperature and species distribution maps, we studied the spatiotemporal variation in the thermal safety margins (TSM, i.e., the difference between T crit , the critical photosynthetic temperature, and the maximum canopy temperature) of 208 tropical tree species in South America, Southeast Asia, and Central Africa during the period 2001–2020. Despite overall high-temperature tolerance with an average T crit of 46.1 ° C, we observed a consistent decline in the TSM of tropical forests across the globe. The average pantropical TSM decline was 0.4 ° C per decade, with the strongest decline in South America ( 0.5 ° C per decade). Over the 20 -y period, areas that experienced canopy temperatures surpassing the average T crit across reported species increased from 43 Mha to 57 Mha in the tropics, representing 4 % of the studied area. This number increases to 10 % when computing areas where temperatures have surpassed the T crit of the most vulnerable reported species. When considering future trends, as predicted by Earth System Models under medium-to-high emission scenarios, average T crit may be exceeded in an area of 83 Mha by 2050 and 160 Mha by 2100 (over 10 % of the studied area), suggesting major feedback to the global carbon cycle and the world’s biodiversity.